PENGARUH GENOTIP CEKAMAN KEKERINGAN DAN TINGKAT NETRALISASI Al TERHADAP PERTUMBUHAN DAN PERAKARAN KEDELAI - Elfi Yenny Yusuf (Jurnal Agro Indragiri, 2019)
Cultivation of plants on dry acid land faces several obstacles, including drought and high Al3 + solubility. The response of soybean to water deficit varies depending on the plant species, the size and duration of stress and the growth phase. The high solubility of Al3 + in the soil is toxic to plants, thus inhibiting root function and growth. The purpose of this study was to study the growth response and tolerance mechanisms of soybeans under drought and aluminum stress conditions. This study used a completely randomized design (CRD) 3 factors with 3 replications, consisting of soybean genotypes (SP 30-4, PG 57-1, Anjasmoro and Tanggamus), drought periods (2, 6 and 10 days), and Al neutralization ( 0 x Aldd and 1 x Aldd). The difference in growth response between genotypes to Al stress and drought was seen in the variables of plant height, number of leaves, and crown dry weight